A study on the wall thickness in the angular deep drawing process - Unal, Engin; Ozek, Cebeli (Carl Hanser Verlag, 2017)
The aim of this paper is the modeling and the corresponding experimental validation of angular deep drawing parameters on the tensile strength, wall thickness and height of the square profile cups. The full factorial experimental method was used to collect the data. FE analysis results were compared with experimental measurements. As a consequence, it was observed that angular deep drawing dies gave better results with different angle values than conventional dies with higher drawing ratios. In general, the product quality increased by an increase of the die/blank holder angle. FEM model results were in good agreement with experimental measurements.
Keywords: Squared cups; sheet metal; deep drawing; wall thickness; FEM